2006
DOI: 10.1111/j.0014-3820.2006.tb00516.x
|View full text |Cite
|
Sign up to set email alerts
|

The Island Rule in Large Mammals: Paleontology Meets Ecology

Abstract: The island rule is the phenomenon of the miniaturization of large animals and the gigantism of small animals on islands, with mammals providing the classic case studies. Several explanations for this pattern have been suggested, and departures from the predictions of this rule are common among mammals of differing body size, trophic habits, and phylogenetic affinities. Here we offer a new explanation for the evolution of body size of large insular mammals, using evidence from both living and fossil island faun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
118
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 173 publications
(125 citation statements)
references
References 76 publications
(114 reference statements)
5
118
0
2
Order By: Relevance
“…Although much study is needed to fully understand patterns of trait evolution and covariation in insular vertebrates, we hope to have shed some light on this complex issue, by showing how disparate factors must be taken into account in order to gain a meaningful depiction of the evolution of life on islands [94]. …”
Section: Discussionmentioning
confidence: 99%
“…Although much study is needed to fully understand patterns of trait evolution and covariation in insular vertebrates, we hope to have shed some light on this complex issue, by showing how disparate factors must be taken into account in order to gain a meaningful depiction of the evolution of life on islands [94]. …”
Section: Discussionmentioning
confidence: 99%
“…The simple scenario that Foster [4] described, in which size increase or decrease predominates within a given order of mammals, has been replaced with the description of a generally monotonic trend of decrease in size ratio with increasing body size across species [5]. This, in turn, has been refined and replaced by models of size change that apply differently in different cases and are contingent both on the phylogenetic affinity of the population and on an array of ecological, environmental, geographical and species-specific attributes of the island þ population pair ( [6 -12]; for more thorough treatments of island rule literature and theory, see [7,13,14]). …”
Section: Introductionmentioning
confidence: 99%
“…Explanations of this kind need to be employed with great care [44], and to explain the island rule, it must be demonstrated that individual selection tends towards the same outcome, or that differential extinction has indeed played an important role. Furthermore, it is not clear that total resource availability is limiting in some well-studied cases [7], [45].…”
Section: Discussionmentioning
confidence: 99%